Electroconvulsive Therapy Handbook - Deisy Santana Castellón; Odalis Fernández López; Juan Rafael Cordero Jiménez; Iris Rodríguez Sánchez; Lenis Cañedo Santana; Rafael Ángel Bello Cruz; Angel Fernández Vidal; Dámaso Molina González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
-